PENGARUH PENYAJIAN ELEMEN-ELEMENT INTEGRATED REPORTING DALAM LAPORAN TAHUNANTERHADAP ASIMETRI INFORMASI (Studi Empiris pada Non Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2015) - Ramadani, Suci; Indrawati, Novita; Darlis, Edfan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research is aimed to examine influence of the presentation of the element-element integrated reporting in the annual report to the asymmetry of information. The research was conducted on a non-financial listed on the Indonesian stock exchange 2015.The population in this study are all non-financial companies listed on the stock exchange Indonesia in 2015 are 440 companies. Samples used in this research are 85 companies. The method of determining the sample is by using a random sampling method, while the data processing method used by reseacher are the multiple regression and use SPSS version 22.00. The result of this research showed that the variable overview of the organization and the external environment, governance, and resource allocation strategy, business model, performance, future outlook no significant effect on information asymmetry. While the risks and opportunities of variables significantly influence the asymmetry of information.Keywords : overview of the organization and the external environment, governance, business model, risk and opportunity strategy and resource allocation, performance, future outlook, the information asymmetry